2009
DOI: 10.1007/s10549-009-0698-1
|View full text |Cite
|
Sign up to set email alerts
|

TNFα −308 G/A polymorphism is associated with breast cancer risk: a meta-analysis involving 10,184 cases and 12,911 controls

Abstract: Tumor necrosis factor a (TNFa) is a pleiotropic cytokine which can regulate a wide variety of cellular responses. Low concentrations of TNFa seem to increase tumor growth and progression. The -308 G/A polymorphism in TNFa has been implicated in breast cancer risk but the published data remain inconclusive. In order to derive a more precise estimation of the relationship, a meta-analysis was performed by searching PubMed, Web of Science, ScienceDirect, EBSCO, CNKI, and Chinese Biomedicine Database. 11 studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Only published studies with available full text articles were included. When overlapping data of the same patient population were included in more than 1 publication, only the literature providing the full text was used in the analysis [2].…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Only published studies with available full text articles were included. When overlapping data of the same patient population were included in more than 1 publication, only the literature providing the full text was used in the analysis [2].…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…So far, the polymorphism TNF-a-238G>A, rs361525 has not been investigated and its relationship with cancer risk has not been understood compared to another important polymorphism, TNF-a-308G/A. In a recent study by Fang et al [2], the association between TNF-a-308G/A and breast tumor risk was confirmed through a meta-analysis. However, the accumu- Guo/Meng/Pei/Zhu tween TNF-a-238G>A and breast cancer risk in Asian women are warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TNF-α induces the expression of adhesion molecules, facilitating the invasion of metastatic tumor cells (Champ et al, 2012). Multiple studies have found a significant association between this cytokine and increased risk for BC (Fang et al, 2010;Shen et al, 2011), and an increase in the severity of the disease (Azmy et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The TNF-α-308G>A polymorphism is located in the promoter region of the gene and involves the substitution of a guanine (G) by an adenine (A). This change effects gene expression, increasing production of TNF-α (Cereda et al, 2012) and has been extensively associated with complex diseases, including BC (Azmy et al, 2004;Fang et al, 2010;Shen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α and LTA polymorphisms were reported to be associated with cancers (Pooja et al, 2010), which had draw many researchers' attentions to in the breast cancer study. Recently, TNF-α polymorphisms were not found to be associated with the risk of BC in two meta-analysis studies (Fang et al, 2010). However, the results were inconsistent and ambiguous for LTA-252 A>G polymorphism studies (the most investigated site) (Park et al, 2002;KamaliSarvestani et al, 2005;Lee et al, 2005;Gaudet et al, 2007;Kohaar et al, 2009;Pooja et al, 2010;Karakus et al, 2011).…”
Section: Introductionmentioning
confidence: 99%